2000
DOI: 10.1111/j.1600-0854.2000.11206.x
|View full text |Cite
|
Sign up to set email alerts
|

GMx33: A Novel Family of trans‐Golgi Proteins Identified by Proteomics

Abstract: The known functions of the Golgi complex include the sorting, packaging, post-translational modification, and transport of secretory proteins, membrane proteins, and lipids. Other functions still remain elusive to cell biologists. With the goal of identifying novel Golgi proteins, a proteomics project was undertaken to map the major proteins of the organelle using two-dimensional gels, to identify the unknowns using tandem mass spectrometry, and to screen for Golgi residents using GFP-fusion constructs. Multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 41 publications
1
36
0
Order By: Relevance
“…b (II) The histogram of apoptosis proportion detected by flow cytometry before or after G3 ShRNA transfection is shown. Apoptosis was detected by annexin V-FITC/PI in the control, OGD/R 4-h, OGD/R 24-h, and corresponding OGD/R groups after G3 ShRNA transfection (*P<0.01 compared to Normal/NC and OGD/R 24-h; # P<0.01 in the OGD/R 4-h groups compared to the OGD/R 24-h groups; n=3, mean± SD) (RQ relative quantification, CON normal control, N.C negative control, ShRNA GOLPH3 ShRNA) maintenance, receptor sorting, protein glycosylation, and the cell signaling pathways that localize to the cytoplasmic face of the trans-Golgi [4][5][6][7][8][9][10][11]. Subcellular localization studies revealed the co-localization of GOLPH3 to the Golgi apparatus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…b (II) The histogram of apoptosis proportion detected by flow cytometry before or after G3 ShRNA transfection is shown. Apoptosis was detected by annexin V-FITC/PI in the control, OGD/R 4-h, OGD/R 24-h, and corresponding OGD/R groups after G3 ShRNA transfection (*P<0.01 compared to Normal/NC and OGD/R 24-h; # P<0.01 in the OGD/R 4-h groups compared to the OGD/R 24-h groups; n=3, mean± SD) (RQ relative quantification, CON normal control, N.C negative control, ShRNA GOLPH3 ShRNA) maintenance, receptor sorting, protein glycosylation, and the cell signaling pathways that localize to the cytoplasmic face of the trans-Golgi [4][5][6][7][8][9][10][11]. Subcellular localization studies revealed the co-localization of GOLPH3 to the Golgi apparatus.…”
Section: Discussionmentioning
confidence: 99%
“…Mammalian GOLPH3, also known as GPP34/GM×33/MI-DAS, is an abundant 34-kDa phosphorylated protein initially identified through a proteomic analysis of detergent-insoluble proteins in an isolated Golgi fraction [4]. It represents an exciting new class of Golgi outer membrane protein involved in vesicular trafficking, Golgi architecture maintenance, receptor sorting, protein glycosylation, and cell signaling pathways that localize to the cytoplasmic face of the trans-Golgi [5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Vps74p bound both the CT of glycosyltransferases as well as to the COPI coat, providing a mechanism by which these enzymes can be incorporated into retrograde transport vesicles [75]. Even though the Vps74p-binding motif is not present in the CTs of mammalian glycosyltransferases, the human orthologs of Vps74p (i.e., Gpp34/ GmX33a and Gpp34R/Gmx33b [79,80]) could still functionally substitute for Vps74p when they where expressed in yeast cells [75]. Although Vps74-like proteins are present in the majority of eukaryotes, which suggests a conserved mechanism, homologs have yet to be identified in higher plants and protozoa, an observation that supports the operation of multiple mechanisms in the retention of glycosyltransferases in the Golgi.…”
Section: The Role Of the Cytoplasmic Tail In Glycosyltransferease Locmentioning
confidence: 99%
“…GOLPH3, also known as GPP34, GMX33, or MIDAS [4,5], is a phosphorylated protein located in the Golgi complex. Schmitz et al previously found that deletion of VPS74, which is a homologue of GOLPH3 in budding yeast, led to defective transition and secretion of glycosylated protein [14], and the authors proposed that GOLPH3 affects glycosyl transferases in the Golgi complex and is therefore involved in protein glycosylation.…”
Section: Discussionmentioning
confidence: 99%
“…Golgi phosphoprotein 3 (GOLPH3) is a highly conserved protein with a molecular weight of 34 kDa [4,5] that is predominantly located in the external membrane of the trans-face of the Golgi, and it was initially identified through a proteomics analysis of the Golgi apparatus [4]. In 2009, Scott et al first reported the overexpression of GOLPH3 in cancer [6].…”
Section: Introductionmentioning
confidence: 99%